please answeerrtrrr
Attachments:
![](https://hi-static.z-dn.net/files/da8/27bacc069f17b8f385a2ce9d32091ddc.jpg)
Answers
Answered by
0
a=-4
d=3
Sn=437
Sn=n/2 [2a+(n-1)d]
Sn=n/2[2×(-4)+(n-1)×3]
Sn=n/2 [(-8)+3n-3]
Sn=n/2[(-11)+3n]
Sn=-11n/2+3n^2/2
Sn=437 (given)
437=-11n/2+3n^2/2
437×2=-11n+3n^2
874=-11n+3n^2
3n^2-11n-874
factorise it .......
d=3
Sn=437
Sn=n/2 [2a+(n-1)d]
Sn=n/2[2×(-4)+(n-1)×3]
Sn=n/2 [(-8)+3n-3]
Sn=n/2[(-11)+3n]
Sn=-11n/2+3n^2/2
Sn=437 (given)
437=-11n/2+3n^2/2
437×2=-11n+3n^2
874=-11n+3n^2
3n^2-11n-874
factorise it .......
Answered by
0
hope this helps...
best of luck....
best of luck....
Attachments:
![](https://hi-static.z-dn.net/files/d07/f790858af5e767f546fba5ef95212581.jpg)
Similar questions
Math,
9 months ago
English,
9 months ago
Chemistry,
1 year ago
Social Sciences,
1 year ago
Physics,
1 year ago